Photoluminescence Tuning Through Irradiation Defects in CH3NH3PbI3 Perovskites - Plantevin, Olivier; Valère, Stéphanie; Guerfa, Driffa; Lédée, Ferdinand; Trippé‐Allard, Gaëlle; Garrot, Damien; Deleporte, Emmanuelle (physica status solidi (b), 2019)
Defect engineering is applied to hybrid (CH3NH3)PbI3 organic–inorganic perovskites. These materials have become one of the most promising low‐cost alternatives to traditional semiconductors in the field of photovoltaics and light emitting devices. Here Helium ion irradiation at low energy has been used as a tool for the controlled introduction of point defects in both single crystals and polycrystalline thin films. The irradiation defects modify the opto‐electronic properties as probed using photoluminescence (PL) spectroscopy from 10 K to room‐temperature. Contrary to usual semiconductors, a very good resilience of the PL properties with irradiation is observed, even associated to an enhancement of the optical emission at low temperature. These results are discussed in relation with the tetragonal to orthorhombic low‐temperature phase transition below T = 160 K. A comparison between spectra from single crystals and polycrystalline films, both with and without irradiation defects, allows a better understanding of the light emission mechanisms in both kinds of samples. The authors thereby evidence radiation hardness of these materials and the specificity of defects and their impact on light emission properties. This work explores the role played by point defects upon light‐emission properties in CH3NH3PbI3 hybrid perovskite materials. Helium ion irradiation at 30 keV has been used for the controlled introduction of defects. Both single crystals and polycrystalline thin films present high radiation hardness, about 105 times higher than crystalline silicon. The authors also show that light emission is enhanced at low temperature by irradiation defects.